Synthesis and characterization of graphene and its composites for Lithium-Ion battery applications: A comprehensive review - L. Syam Sundar; M. Amin Mir; M. Waqar Ashraf; Faramarz Djavanroodi (Alexandria Engineering Journal, 2023)
In recent years, the demand for high performance rechargeable lithium-ion batteries has grown dramatically and numerous initiatives were taken to enhance the usage of cutting edge electrical conducting materials. The graphene and graphene-based materials have undergone further investigation since their discovery, and as a result, they are now recognized as high performance electro-conductance materials. Graphene is known as a 2-dimensional carbon-based material with an existing of high Young's modulus, outstanding electrical conductivity, amazing intrinsic electron mobility, enhanced mechanical strength, enhanced photosensitive transmittance, catalytic activity and chemical stability. However, in the past ten years, both the applied materials industry and academia have achieved remarkable innovations as a result of the use of graphene, despite some challenges that include high production cost that are incurred at the expense of compromised high-quality materials. Also, scarce availability in large amounts necessary for mass distribution is among the challenges is among the graphene producing challenges. In this review paper, we emphasize the recent functionalization developments, controlled product materials, and the usage of graphene in rechargeable lithium-ion batteries. In order to describe the future development of graphene for lithium-ion batteries, we will discuss the most encouraging outcomes, advantages, difficulties, crucial problems, research areas, and perspectives in this review.